Pandemic Pressure: Changes in Hypertensive Management Adherence in Indonesia - Dwi H. Tjandrarini; Dewi Kristanti; Tri Wurisastuti; Puti S. Hidayangsih; Sulistyowati Tuminah; Astridya Paramita; Ina Kusrini; Ika Dharmayanti; Frans Dany; Feri Ahmadi; Christiana R. Titaley (Elsevier, 2024)
s u m m a r y: Purpose: This study aimed to determine factors associated with changes in adherence to hypertension management (medication adherence and blood pressure control) in respondents with hypertension before and during the COVID-19 pandemic in Bogor city, Indonesia. Methods: An observational study was conducted using two sources of data (before and during COVID-19 pandemic). Data before the pandemic were derived from the 2019 Cohort Study of non-communicable disease risk factors. Data during the pandemic were derived from an online survey conducted in September and October 2020. Information from 880 participants were analyzed. The dependent variable was the change in adherence to hypertension management before and during the COVID-19 pandemic. Multivariate analysis was performed using logistic polynomial regression. Results: Respondents who adhered to hypertension management decreased from 82.0% in 2019 to 47.8% in 2020. The likelihood of non-adherence (respondents who did not adhere to hypertension management both before and during the pandemic) increased in respondents below 55 years old, who did not own any healthcare insurance, who were not obese, and who had no other comorbidities. In the partial adherence group (respondents who did not adhere to hypertension management either before or during the pandemic), we found that most respondents adhered before the pandemic but no longer adhered during the COVID-19 pandemic. We found an increased partial adherence in young and highly educated respondents. Conclusions: Efforts to improve adherence to hypertension management after the COVID-19 pandemic should target those who were young, highly educated, who did not have any healthcare insurance, and who did not perceive themselves as not having comorbidities.